THE UNDERSTANDING OF ḤUDÛD ALLÂH IN THE QURAN: Study of Thematic-Contextual Interpretation - Bakheet Ahmed, Bakrei Mohammed (ULUL ALBAB Jurnal Studi Islam, 2020)
The term ḥudûd Allâh is one of those written in al-Quran al-Karim used for clarifying the laws. However, some people do not quite comprehend this term that their understanding is only limited to the law related to criminal (penalty), meanwhile Quran does not limit the term only for penalty. Therefore, the author chose the title to explain the ḥudûd Allâh term mentioned in Quran and its meanings in some parts using empirical and inductive methods in quoting opinions of mufassir both in the classic and contemporary generations. In this article, the author divides it into four discussions related to the theme in the verses. The crucial conclusion of this article is that the ḥudûd Allâh term in Quran never refers to criminal law such as the penalty for adultery, liquor, and the like. On the other hand, the term is to explain the laws of family matters, ahwal shahsiyah e.g. divorce, ‘iddah (waiting period), filing divorce from the wife side, inheritance distribution, and general meaning on Allah’s orders and prohibitions.